Personal Branding Content Creator di Media Sosial Instagram - Debora Lois; Diah Ayu Candraningrum (Koneksi, 2021)
Content creator has become a new profession that is in great demand. Titan Tyra is one of Indonesia's content creators. Titan Tyra's Instagram account has now reached 616,000 followers. Content uploaded through Instagram stories such as endorsement content, vlogs of daily activities, fashion style, and make-up. Social media is a means of support and media for content creators as a forum for expressing ideas, works and art in the form of videos, photos or pictures, writing, and other visualizations. This research discusses Titan Tyra's personal branding in the social media account of Instagram @titantyra. The research objective was to conduct research to determine Titan Tyra's personal branding on Instagram. Primary data were obtained from interviews with three Titan Tyra followers. In this case the researcher wants the perspective of Titan Tyra's followers. The theory used is Peter Montoya's Theory (The Eight Laws Of Personal Branding), data analysis techniques using qualitative research, case study research methods with personal branding analysis. The results of this study indicate that Titan Tyra fulfills eight principles of personal branding such as Specialization (The law of specialization), Leadership (The law of leadership), Personality (The law of personality), Difference (The law of distinctiveness), Visible (The law of distinction).  visibility), Unity (The law of unity), Firmness (The law of persistence), Good name (The law of goodwill).Content creator sudah menjadi profesi baru yang banyak diminati. Titan Tyra merupakan salah satu content creator Indonesia. Akun Instagram Titan Tyra saat ini sudah mencapai 616.000 pengikut. Konten-konten yang diunggah melalui instastory Instagram seperti konten endorse, vlog kegiatan sehari-hari, fashion style, dan make-up. Media sosial merupakan sebuah sarana penunjang dan media bagi content creator sebagai wadah untuk menuangkan ide-ide, karya, dan seni dalam bentuk video, foto atau gambar, tulisan, dan visualisasi lainnya. Penelitian ini membahas tentang personal branding Titan Tyra diakun media sosial Instagram @titantyra. Tujuan penelitian ini untuk mengetahui personal branding Titan Tyra di Instagram. Data primer diperoleh dari hasil wawancara tiga orang followers Titan Tyra. Dalam hal ini peneliti menginginkan sudut pandang followers Titan Tyra. Teori yang digunakan adalah Teori Peter Montoya (The Eight Laws Of Personal Branding), teknik analisis data menggunakan penelitian kualitatif, metode penelitian studi kasus dengan analisis personal branding. Hasil penelitian ini menunjukkan bahwa Titan Tyra memenuhi delapan prinsip personal branding seperti: spesialisasi (the law of specialization), kepemimpinan (the law of leadership), kepribadian (the law of personality), perbedaan (the law of distinctiveness), terlihat (the law of visibility), kesatuan (the law of unity), keteguhan (the law of persistence), dan nama baik (the law of goodwill).